Are inequality and trade liberalization influences on growth and poverty? - Jennifer Mbabazi; Oliver Morrissey; Chris Milner (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
There has been a recent resurgence of interest in the relationship between income inequality and growth, manifested in a number of important publications. In parallel with this, concern with the impact of economic reform and globalization on developing countries has led to an upsurge of interest in linkages between policy reform, growth, inequality and poverty. We use the WIDER/UNDP World Income Inequality Database to investigate the links between growth, inequality and trade liberalization for a sample of developing countries, and the more limited World Bank Global Poverty Monitoring Database for an exploratory analysis of the influence of these variables on levels of poverty. The cross-section results suggest that in the long-run, higher inequality is associated with lower growth. There is weak evidence that openness is associated with higher growth. A panel analysis suggests that inequality is unrelated to growth in the shortrun, although trade liberalization appears to have a positive impact on growth. Regarding poverty, the only consistent patterns are that higher levels of human capital are associated with lower levels of poverty, while poverty is higher in sub-Saharan Africa. There is no evidence that growth and trade liberalization affect poverty, although countries that have sustained an open trade regime appear to have lower levels of poverty. – trade ; inequality ; growth ; poverty ; developing countries
Keywords: F14; F43; O15; O40; 330; Wirtschaftswachstum; Armut; Einkommensverteilung; Außenhandelsliberalisierung; Entwicklungsländer